Neonatal Bartter Syndrome - Roy, Amrita; Chakraborty, Debalina Sarkar; Dogra, Shivani; Sengupta, Sudip (Journal of Nepal Paediatric Society, 2016)
The neonatal form of Bartter syndrome is characterized by intrauterine onset of polyuria leading to severe polyhydramnios. We report a case of a 31 weeks, male baby was born by emergency Caesarean Section due to severe polyhydramnios (AFI 54). Postnatally, baby had polyuria, dehydration, hyponatremia, hypokalemia and hypochloremic metabolic alkalosis. Possibility of neonatal Bartter syndrome was supported by high serum renin and aldosterone levels. Correction of electrolytes and dehydration along with indomethacin constituted the treatment. This syndrome is reported to make paediatricians aware about the severe neonatal form of the disease. J Nepal Paediatr Soc 2016;36(2):204-207.